Rickettsial Infectious Antibody Complexes: Detection by Antiglobulin Plaque Reduction Technique - Kenyon, Richard H. (1974)
Rickettsia rickettsii and R. australis formed infectious antibody complexes when reacted with homologous convalescent serum. The addition of antiglobulin to these complexes showed neutralization of plaques proportional to the concentration of rickettsial immune serum.